Pengaruh Gaya Hidup Dan Literasi Keuangan Terhadap Perilaku Konsumtif Berbelanja Online (Studi Kasus pada Mahasiswa Fakultas Ekonomi dan Bisnis Unisma) - Rachman, Muchammad Zidane; Priyono, Achmad Agus; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to analyze and describe the influence of Lifestyle and Financial Literacy on Consumptive Behavior in online shopping (case study of Unisma Faculty of Economics and Business Students). The population in this research is FEB UNISMA students who have shopped online. Determining the number of samples used the Malhotra formula and obtained results of 60 respondents. Data collection was carried out using a questionnaire. To solve the problem in this research using SPSS assistance with the analytical methods used in this research are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, F test, t test, coefficient of determination test (R2) . The research results show that Lifestyle has a significant effect on Consumptive Behavior, while Financial Literacy has no significant effect on Consumptive Behavior. Keywords: Consumptive Behavior, Lifestyle and Financial Literacy.